2019
DOI: 10.4067/s0719-81322019000200061
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of yield characteristics of Damascus and Kilis goats in dry climatic conditions

Abstract: The aim of this study was to compare the reproductive traits, lactation milk yield, and body measurements of the Damascus (Shami) and Kilis goats raised as dairy goats in the dry climatic conditions of the Southeastern Anatolia region of Turkey. The study was perfomed using 596 Damascus goats and 82 Kilis goats between 3-5 years old. It was observed that the lactation milk yield, lactation period, withers height, and leg circumference of the Damascus goats (175.86 kg, 227.48 days, 72.67 cm, and 74.10 cm, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…These results demonstrate how good the growth performance of Cyprus Native Hair Goats can be. [24] for the Turkish Damascus Goat breed in Diyarbakir Province, the results found in this study for wither height, body length, chest depth, chest width, and heart girth in Cyprus Native Hair Goats seem to be higher, particularly in males of 4 years of age. So logically, the body weight of this breed was much…”
Section: Cyprus Native Hair Goats Body Measurementssupporting
confidence: 57%
“…These results demonstrate how good the growth performance of Cyprus Native Hair Goats can be. [24] for the Turkish Damascus Goat breed in Diyarbakir Province, the results found in this study for wither height, body length, chest depth, chest width, and heart girth in Cyprus Native Hair Goats seem to be higher, particularly in males of 4 years of age. So logically, the body weight of this breed was much…”
Section: Cyprus Native Hair Goats Body Measurementssupporting
confidence: 57%
“…The goat milk yield and milk composition depend on genetic and non-genetic factors (Taiwo Idowu and Olufunke Adewumi, 2017). Different goat breeds have different milking potentials (Curro et al, 2019;Tatar et al, 2019; Taiwo Idowu and Olufunke Adewumi, 2017). This is possible because their genomes are different.…”
Section: Introductionmentioning
confidence: 99%
“…This value was similar to the value of 300 days determined in Damascus goats in the hands of the public in Lebanon (Khazaal, 2009). However it was higher than the values of 227.48 days and 170.39 days determined respectively in Damascus and Kilis goats grown in Turkey (Tatar et al, 2019), 176 days and 183 days found respectively in one year old and two years old goats grown in Cyprus (Mavrogenis and Constantinou, 1982), and 254.7±2.359 days determined in those grown in Northern Cyprus (Guney et al, 2006).…”
Section: Resultsmentioning
confidence: 63%